Fabrication and characterisation of additive manufactured PH15-5 parts via directed energy deposition - Quek, Shao Xuan (2019)
Directed energy deposition (DED) is a type of additive manufacturing (AM) process categorized under the ASTM standards. In DED, metal powder is deposited through a coaxial nozzle and melted with a laser, building the part layer by layer, with the capability to fabricate up to 99% dense parts. The aim of this study is to determine the effects of different initial laser power on the build, sample parts that were printed with decreasing laser power while maintaining the melt pool temperature. These samples were fabricated with three different temperature gradients before maintaining it at a constant power. The microstructure of the segmented parts were observed and analysed. Density and hardness of the samples are some of the properties that were investigated to understand how change in power affect these properties. The results show that a time-variant process control over the input power can be a good method of fabrication, as results revealed that porosities can be reduced and metallurgical microstructure homogeneity can also be achieved. However, sufficient energy must still be maintained to accomplish such results.